2021
DOI: 10.1021/acsami.1c18750
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible All-in-One Adhesive Needle-Free Cup Patch for Enhancing Transdermal Drug Delivery

Abstract: Patch-type drug delivery has garnered increased attention as an attractive alternative to the existing drug delivery techniques. Thus far, needle phobia and efficient drug delivery remain huge challenges. To address the issue of needle phobia and enhance drug delivery, we developed a needle-free and self-adhesive microcup patch that can be loaded with an ultrathin salmon DNA (SDNA) drug carrier film. This physically integrated system can facilitate efficient skin penetration of drugs loaded into the microcup p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Dissolving microneedles are a patch-type drug delivery system that requires an adhesive film that adapts well to the skin and does not easily fall off to achieve ideal penetration and fixation. , The developed film has the advantage that it can be integrated into the dissolving microneedle manufacturing process as a biocompatible asymmetric adhesive film, which is an essential element of such drug delivery systems. Figure a shows the process for combining microneedles and the prepared attachable film, and how to attach it to the skin.…”
Section: Resultsmentioning
confidence: 99%
“…Dissolving microneedles are a patch-type drug delivery system that requires an adhesive film that adapts well to the skin and does not easily fall off to achieve ideal penetration and fixation. , The developed film has the advantage that it can be integrated into the dissolving microneedle manufacturing process as a biocompatible asymmetric adhesive film, which is an essential element of such drug delivery systems. Figure a shows the process for combining microneedles and the prepared attachable film, and how to attach it to the skin.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional local oral mucosal treatments include film administration and local injection . The typical film administration is noninvasive, and gels, ointments, and patches , are used. However, the osmotic barrier formed by the outermost layer of the oral mucosa affects the efficiency of local administration .…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Furthermore, wearable transdermal drug delivery system (TDDS) has been prevalent for noninvasive and stimuli‐responsive drug release via permeating skin structure to the bloodstream, enabling treatment on purpose (auto‐medication). [ 4 ] Numerous recent studies reported various types of skin‐patchable devices for different biomedical applications, including drug delivery, [ 2,5 ] wound healing, [ 6 ] treatment of myocardial infarction, [ 7 ] and tissue engineering. [ 8 ] To this end, advanced technologies from different fields, including selection of correct materials (e.g., biopolymers and nanomaterials), [ 9 ] adopting suitable fabrication methods (e.g., soft lithography and 3D printing) [ 10 ] and designing specific biochemical reactions have been to fabricate functional skin patches for transdermal theragnostics.…”
Section: Introductionmentioning
confidence: 99%